Maxillary Reconstruction using Chimeric Flaps of the Subscapular Artery System without Vein Grafts and the Novel Usage of Chimeric Flaps - Watanabe, Koichi; Takahashi, Nagahiro; Morihisa, Yoichiro; Ikejiri, Mitsuhiro; Koga, Noriyuki; Rikimaru, Hideaki; Kiyokawa, Kensuke (Journal of Reconstructive Microsurgery, 2013)
The purpose of this study was to overcome the disadvantages associated with the shortness of the vascular pedicle of subscapular system combined flaps when performing the maxillary reconstruction procedure. Combined flaps of the subscapular artery system were used for maxillary reconstruction. A latissimus dorsi myocutaneous flap, a scapular fasciocutaneous flap, and two kinds of scapular bone flaps were elevated as combined flaps. Next, the circumflex scapular artery (CS) and vein were cut off from the combined flaps and anastomosed to the serratus anterior branch, thereby establishing chimeric flaps. Then, maxillary reconstruction was performed using these flaps. We encountered two patients who underwent maxillectomy for maxillary cancer. Satisfactory improvements in facial shape were obtained in both cases. In cases in which combined flaps of the subscapular artery system are used for maxillary reconstruction, the biggest problem is that the vascular pedicle does not reach the recipient vessel in the neck due to the shortness of the CS. Therefore, vein grafts are generally performed to extend the flaps to the maxilla. Our novel procedure has the great advantages of long vascular pedicles and high flexibility in setting the flaps without the use of vein grafts.
Keywords: maxillary reconstruction; chimeric flaps; subscapular artery system; serratus anterior branch; scapular bone flap